USING NON-DIALOGUE SHORT ANIMATED STORIES AS A TEACHING MEDIA TO IMPROVE NARRATIVE TEXT WRITING SKILL OF THE TENTH GRDERS OF SMA EL SHADAI MAGELANG IN THE SCHOOL YEAR 2017/2018 - Bayu Fatkhurahman (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
Most students get difficulties in writing English especially narrative text. There are internal and external factors which influence students’ skill. One of them is the teaching media that is used by the teacher, so the writer conducts this research to overcome the problem by applying the Non-Dialogue Short Animated Stories media.The main objectives of this research; the first is to know whether the Non-Dialogue Short Animated Stories media can increase the student’s learning motivation of the narrative text writing skill and the second is to know how great the improvement of the students’ narrative text writing skill, taught by the Non-Dialogue Short Animated Stories media.The writer conducted a classroom action research which was divided into Pre-cycle, Cycle I, and Cycle II. The writer took 22 students of the tenth grade in SMA El Shadai Magelang as the subject of the research. The writer used non-test and test to collect the data.The result shows that the use of the Non-Dialogue Short Animated Stories media can increase the students’ learning motivation. They were more active and had higher motivation to study. The result of the test, the students’ average score of all cycles; Pre-Cycle (62.95), Cycle I (71.36), Cycle II (82.50). The improvement from Pre-Cycle to Cycle I is 8.41 points. The improvement from Cycle I to Cycle II is 11.14 points. The total of the improvement from Pre-Cycle to Cycle II is 19.55 points.